Drug metabolism alterations in nonalcoholic fatty liver disease - Merrell, Matthew D. (2011)
Drug-metabolizing enzymes play a vital role in the elimination of the majority of therapeutic drugs. The major organ involved in drug metabolism is the liver. Chronic liver diseases have been identified as a potential source of significant interindividual variation in metabolism. Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the United States, affecting between 60 and 90 million Americans, yet the vast majority of NAFLD patients are undiagnosed. NAFLD encompasses a spectrum of pathologies, ranging from steatosis to nonalcoholic steatohepatitis and fibrosis. Numerous animal studies have investigated the effects of NAFLD on hepatic gene expression, observing significant alterations in mRNA, protein, and activity levels. Information on the effects of NAFLD in human patients is limited, though several significant investigations have recently been published. Significant alterations in the activity of drug-metabolizing enzymes may affect the clearance of therapeutic drugs, with the potential to result in adverse drug reactions. With the enormous prevalence of NAFLD, it is conceivable that every drug currently on the market is being given to patients with NAFLD. The current review is intended to present the results from both animal models and human patients, summarizing the observed alterations in the expression and activity of the phase I and II drug-metabolizing enzymes.